Vitrification of day 7 hatching blastocyst using hemistraw resulting in a full term delivery: a case study - Lad, Nitin; Lad, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is probably the first report of a successful delivery following transfer of a vitrified-warmed day 7 slow growing hatching blastocyst using hemistraw-vitriplug as an embryo carrier system. Case Report: A 26 years old Indian woman underwent controlled ovarian stimulation using short antagonist protocol and on day 11 after hCG administration, sixteen mature oocytes obtained were fertilized by ICSI procedure. On day 5, after transfer of two expanded blastocysts, three supernumerary embryos were still in the expanding stages, therefore, continued to culture in vitro. On day 7, one of them grew to be a hatching blastocyst which was cryopreserved with caution by ultra-rapid vitrification using hemistraw (HS) as carrier system. After 5 months, the vitrified slow growing day 7 hatching blastocyst was warmed and transferred in a natural cycle resulting in successful pregnancy. The women delivered a healthy male baby weighing 2820 grams at 36 weeks of gestation by caesarean section with no obvious anomalies detected. This report concludes that a day 7 hatching blastocyst can be successfully vitrified using HS and have pregnancy potential after warming.